ID 417 – Dysphagia in Myotonic Dystrophy type 1: Preliminary results of an integrated neurophysiological and swallowing protocol. Issue 3 (March 2016) - Zardoni, M.; Raimondi, E.; Bruno, S.; Nascimbene, C.; Pasanisi, M.B.; Morandi, L.; Gianelli, F.; Colombo, M.; Schindler, A.; Mariani, C.; Osio, M.
Abstract : Dysphagia is common and under-diagnosed in Myotonic Dystrophy (DM1), leading to nutritional derangement and ab-ingestis pneumonia. Objective: To define the prevalence of dysphagia and to understand underlying mechanisms through an integrated swallowing evaluation in DM1 patients. Methods: Laryngeal accelerometric sensor, submental and cricopharyngeal (CP) muscles EMG to evaluate Dysphagia Limit (DL) (volume at which a second swallow becomes necessary to swallow a water bolus) and swallowing jitter; needle EMG of genioglossus muscle (G-EMG); fiberoptic endoscopic swallowing evaluation (FEES), clinical swallowing scales. Results: 10 DM1 patients (6M-4F, mean age 46 ± 10), compared to 6 healthy subjects (3M–3F, mean age 30 ± 3), showed myotonic discharges (9/10 patients) in G-EMG; reduction in DL in all DM1 patients; abnormal swallowing jitter in 6/10 patients, 5 of them showing anomalies in temporal features of the swallowing reflex; CP-myotonia in 3 patients. 2 patients did not show dysphagia at FEES; penetration signs in 4 and 5 patients respectively with liquids and semisolids. Conclusion: swallowing problems are common in DM1, DL and swallowing jitter are the most sensitive altered parameters. We are extending this protocol to a larger cohort of patients. Key message: Dysphagia is under-diagnosed in DM1 patients. Our neurophysiological evaluation could be an helpful tool in diagnosis of dysphagia and prevention of complications.